ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA POKOK BAHASAN KOMPOSISI FUNGSI DI SMK BAKTI PURWOKERTO - Utami, Arum Setya (AlphaMath : Journal of Mathematics Education, 2018)
This research aims to know the errors of students in solving the question of the story the subject of composition of functions. This research is a descriptive qualitative research qualifies. The subject of this research is the grade XI SMK Bakti Purwokerto. Based on the results of the analysis of the answers to questions given to students, other forms of errors committed students is an error stating the problem, determine what the error was asked from a problem, understand the error information of a problem, and not careful in counting. Keyword: error analysis, a matter story, composition of functions